APPLICATION OF REMOTE SENSING IMAGERY AND GIS IN ESTABLISHMENT OF FOREST FIRE HAZARD MAP IN DAKLAK PROVINCE - Anh, Luu The; Tuan, Tran Anh; Ngoc, Hoang Thi Huyen; Bien, Le Ba (Vietnam Journal of Earth Sciences, 2014)
Forest fire is one of the disasters causing threats to the forests and the ecosystem and socio-economic aspects throught out the world. Forest fire also leads to an increase in green house gases emisstions. Air pollution due to smoke causes prolonged effects on human health such as respiratory and cardiovascular problems. Knowledge of flammable materials and their potential fire behavior in different forest types is essential in forest fire management. Remote Sensing and GIS can play an important role in detecting burnt forest and developing the spatial models to predict potential forest for fire risk. This study demonstrates the effective use of remote sensing imagery and geographic information system for establishing the forest fire hazard map at scale of 1:100.000 for Daklak province. Landsat ETM image captured in 2011 and Weighted Overlay tool in ArcGIS software were used in this study. Eight parameters of forest types, daily average temperature during dry season, daily average precipitation in dry season, daily average wind speed, slope, terrain direction, distant between burned field to forest and distant from resident to forest were used as main inputs in GIS model. The study result shown that, the total fire area at low fire risk is 219,344 ha (accounting for 35.9% of total area of forest in Daklak province), medium fire risk is 130,207 ha (21.3%), high fire risk is 220,565 ha (36.1%) and very high fire risk is 41,488 ha (6.8%). References Amparo, A.B., Oscar, F.R., 2003. An intelligent system for forest fire risk prediction and fire fighting management in Galicia. Expert Systems with Applications 25(6), 545-554. Chuvieco, E., Congalton, R.G., 1989. Application of remote sensing and geographic information systems to forest fire hazard mapping. Remote Sensing of the Environment 29, 147-159. Dong, X.U., 2005. Forest fire risk zone mapping from satellite images and GIS for Baihe Forestry Bureau, Jilin, China. Journal of Forestry Research 16(3), 169-174. Gholamreza, J.G., Bahram, G., Osman, M.D., 2012. Forest fire risk zone mapping form Geographic Information System in Northern Forests of Iran (Case study, Golestan province). International Journal of Agriculture and Crop Science 4(12), 818-824. Phạm Ngọc Hưng, 2001. Thiên tai khô hạn cháy rừng và giải pháp phòng cháy chữa cháy rừng ở Việt Nam. Nxb. Nông nghiệp, Hà Nội, 224tr. Phạm Ngọc Hưng, 2004. Quản lý lửa rừng ở Việt Nam. Nxb. Nghệ An, 231tr. Jaiswal, R.K., Mukherjee, S., Raju, D.K., Saxena, R., 2002. Forest fire risk zone mapping from satellite imagery and GIS. International Journal of Applied Earth Observation and Geoinformation 4, 1-10. Lazaros, S.I, Anastaios, K.P., Panagiotis, D.L., 2002. A computer-system that classifies the prefectures of Greece in forest fire risk zones using fuzzy sets [J]. Forest Policy and Economics 4, 43-54. Mariel, A., Marielle, J., 1996. Wildland fire risk mapping using a geographic information system and including satellite data: Example of "Les Maures" forest, south east of France [J]. EARSeL Advances in Remote Sensing 4(4), 49-56. Shailesh Nayak, Sisi Zlatanova, 2008. Remote sensing and GIS technologies for monitoring and prediction of disasters. Springer-Verlag Environment Science and Engineering, 127pp. William, A.T., Ilan, V., Hans, S., 2000. Using forest fire hazard modeling in multiple use forest management planning [J]. Forest Ecology and Management 134(2), 163-176. Bộ Nông nghiệp và Phát triển nông thôn, 2004. Cẩm nang ngành lâm nghiệp - Chương "Phòng cháy và chữa cháy rừng". Chương trình hỗ trợ ngành lâm nghiệp và đối tác, 89tr. Chi cục Kiểm lâm Đắk Lắk, 2012. Báo cáo chuyên đề "Thực trạng cháy rừng, nguyên nhân và các giải pháp phòng cháy chữa cháy rừng". Tài liệu lưu trữ tại Viện Địa lý, 27tr.